2000
DOI: 10.1038/eye.2000.156
|View full text |Cite
|
Sign up to set email alerts
|

The role of tear physiology in ocular surface temperature

Abstract: Purpose To determine whether the more rapid cooling of the tear film in dry eyes is related to other tear film parameters, a battery of tear physiology tests was performed on dry eye patients and control subjects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
106
2
3

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 167 publications
(117 citation statements)
references
References 29 publications
2
106
2
3
Order By: Relevance
“…25,26 In addition, the lid changes occurring in course of MGD such as thickening, hyperaemia, and eyelash malposition may contribute to the signs of ocular irritation often occurring in these patients, resulting from irregular lid margin and consequent inefficient tear distribution over the ocular surface. [27][28][29] In the present study, a lower tear basal secretion and more evident conjunctival alterations were observed in subjects with MGD; these findings may also contribute to the presence of ocular discomfort symptoms during the work at VDT.…”
Section: Discussionmentioning
confidence: 51%
“…25,26 In addition, the lid changes occurring in course of MGD such as thickening, hyperaemia, and eyelash malposition may contribute to the signs of ocular irritation often occurring in these patients, resulting from irregular lid margin and consequent inefficient tear distribution over the ocular surface. [27][28][29] In the present study, a lower tear basal secretion and more evident conjunctival alterations were observed in subjects with MGD; these findings may also contribute to the presence of ocular discomfort symptoms during the work at VDT.…”
Section: Discussionmentioning
confidence: 51%
“…Changes in OST can be contributed by tear film instability and rapid tear evaporation [9,18]. Others have reported contrary findings.…”
Section: Correlation Between T4 Metrics and Signs And Symptoms For Drmentioning
confidence: 79%
“…Ocular surface temperature (OST) measurement with infrared (IR) ocular thermography is indicative of the tear film and its stability [9,10]. Ocular thermography has been used to study DED [9,[11][12][13][14][15][16][17][18][19] with three studies reporting on its diagnostic ability [16,18,19] with inconsistent results. We have also considered the application of IR ocular thermography in screening mild to moderate DED.…”
Section: Introductionmentioning
confidence: 99%
“…23,24 Thin lipid layers (r60 nm) have been correlated with tear film instability, 23,24 increased evaporation rate, 23 high osmolality, 34 symptoms, 24,25 and dry eye disorders. 25 The correlation coefficients in this study for LLT with STA and LLT with FBUT were higher than for STA with FBUT.…”
Section: Discussionmentioning
confidence: 99%